Influence of age, alcohol consumption and abstinence on the sensitivity of carbohydrate-deficient transferrin, γ-glutamyl-transferase and mean corpuscular volume - Mundle, Götz; Ackermann, Klaus; Munkes, Jörg; Steinle, Daniela; Mann, Karl (Alcohol and alcoholism, 1999)
Abstract. Duration of abstinence before blood test, alcohol consumption and age was examined in 177 male alcohol-dependent patients as factors influencing serum